ADHD and Suicidal Ideation: The Roles of Emotion Regulation and Depressive Symptoms Among College Students. (August 2015) - Van Eck, Kathryn; Ballard, Elizabeth; Hart, Shelley; Newcomer, Ali; Musci, Rashelle; Flory, Kate
Objective: ADHD appears to increase risk for both depression and suicidal ideation, while ADHD and depression are also associated with emotion regulation deficits. Thus, we evaluated the degree to which depression mediated the association between ADHD and suicidal ideation, as well as the degree to which emotion regulation deficits moderated the association ADHD shared with depression and suicidal ideation in a nonclinical sample.Method: Participants were undergraduate psychology students ( N = 627; age: M = 20.23, SD = 1.40; 60% female; 47% European American) who completed an online assessment.Results: Results indicated that ADHD indirectly increased suicidal ideation through depression. Emotion regulation deficits of accepting negative emotions, emotional awareness, and goal-oriented behavior moderated the indirect effect of ADHD on suicidal ideation.Conclusion: Depression appears to play an important mediating role in suicidal ideation for college students with ADHD, and specific emotion regulation deficits appear to amplify the effects of ADHD on depression and suicidal ideation.